ROTATSIZM HÁM ONI SAPLASTIRIWDA QOLLANILATUǴIN USILLAR - Tàjimuratov, A.J.; Sharipova, N.K. (SCIENCE and SOCIETY, 2023)
In this article, a wide range of information is given about dyslalia, the children with pronunciation defects, as well as the spread of this defect in society, its prevention, and correctional and speech therapy work carried out with them.